The Implementation of the Jigsaw Cooperative Learning Model to Improve Students' Learning Outcomes in Oily and Acne-Prone Skin Care Using Technology at SMK Negeri 27 Jakarta - Putri Meisya Rustoyo Darmawan; Elvyra Yulia; Dwi Atmanto (Vifada Journal of Education, 2026)
This classroom action research aims to improve the learning outcomes of eleventh-grade students in the Beauty Therapy Program at SMK Negeri 27 Jakarta in the subject of Oily and Acne-Prone Facial Skin Treatment using Technology through the implementation of the Jigsaw cooperative learning model. The study was initiated due to low student learning outcomes and active participation, resulting from initial learning processes dominated by conventional lectures and students' difficulties in operating beauty technology equipment. Conducted in two cycles using the Kemmis and Taggart model, this research involved 34 students as research subjects. The results demonstrated a significant, gradual improvement in learning outcomes across three main domains from pre-cycle to Cycle I and Cycle II. The students' average cognitive score increased from 74.15 (pre-cycle) to 80.74 (Cycle I) and reached 87.91 in Cycle II, with the classical completeness percentage rising sharply from 70.59% to 97.06% by the end of the final cycle. This improvement was also accompanied by positive developments in the affective domain, which showed strengthened discipline, responsibility, and teamwork, as well as in the psychomotor domain, which demonstrated enhanced operational skills in using electrical beauty devices (such as high frequency and galvanic) in accordance with Standard Operating Procedures (SOP). In conclusion, the implementation of the Jigsaw cooperative learning model is effective in optimizing active participation and enhancing the quality of student learning outcomes.